THE INFLUENCE OF GASTRONOMIC OFFER AND SERVICES ON THE BRANDING OF HOTEL DIVČIBARE - Vujić, Tamara; Vujić, Milan; Zrnić, Miloš; Gajić, Tamara; Vukolić, Dragan (The Business of Tourism, 2022)
The gastronomic offer and restaurant service have always played a very important role in the branding of the hotel facilities. The following scales and methods used in paper to obtain research answers are: Demographic analysis, Correlation analysis, Mann Whitney test, Likert scales, Pearson’s coefficient. Based on conducted research, respondents indicated that hotel gastronomic offer, loyalty, satisfaction and services provided, can greatly affect the branding of hotel Divčibare. The survey was conducted in September 2022 on a sample of 250 respondents. This study demonstrates how the caliber of the service and culinary selection affects the respondents’ pleasure and guests’ loyalty. The addition of the study to the body of current knowledge, the contribution to more significant future research, and the identification of strategic solutions for improved hotel operations all serve as indicators of its significance.